High intensity interval training leads to greater improvements in acute heart rate recovery and anaerobic power as high volume low intensity training - Stöggl, T. L.; Björklund, G. (Frontiers in Physiology, 2017)
The purpose of the current study was to explore if training regimes utilizing diverse training intensity distributions result in different responses on neuromuscular status, anaerobic capacity/power and acute heart rate recovery (HRR) in well-trained endurance athletes.